A transducer positioning method for transcranial focused ultrasound treatment of brain tumors - Gao, Penghao; Sun, Yue; Zhang, Gongsen; Li, Chunsheng; Wang, Linlin (Frontiers in Neuroscience, 2023)
The treatment of brain tumors is a complex process due to the complexity of brain tissue, and transcranial focused ultrasound has been proposed as a non-invasive method of regulation that could inhibit tumor activity in the target region by taking advantage of its mechanical and cavitation effects. In this study, we employ a novel RP method to accurately predict the transducer matrix and thereby achieve precise positioning of the ultrasound pathway. The main focus lies in investigating the intensity and safety of ultrasound stimulation. The findings reveal that the optimal pathway outside the target region of temporal lobe tumors to the coronal plane did not exceed 10° and 15° to the transverse plane. The results showed that the positioned ultrasound transducer can be most effective without damaging the brain tissue surrounded the target region due to the heat generated during the process.